Vascular Endothelial Growth Factor (VEGF) Expression on Placenta Accreta Spectrum (PAS) FIGO Grading (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aims to analyze the role of placenta VEGF level using immunocytochemical techniques andcomparing the obtained results with PAS FIGO grading. This retrospective cross sectional study ontotal sampling of formalin fixed paraffin-embedded tissue from placenta sampling of elective surgerywhich were diagnosed as PAS. Sample were immunostained using VEGF and semi-quantitativelyImmuno Reactive Score (IRS) measured based on modified Remmele scale index. The result obtained32 samples that meet inclusion criteria which are found into grade I (n=5), grade II (n=11) and gradeIII (n=16). This study showed average VEGF at grade I (4.68±1.03), grade II (3.81±1.41), grade III(4.46±1.82) and no significant difference of VEGF expression between grade I, grade II and grade III(p = 0.264). Intraplacental VEGF do not describe the severity of PAS FIGO grading.
Keywords: Grading, placenta accreta, VEGF